Causal Factors Affecting Customer Satisfaction through Customer Experience in the B2B of Pharmacy Business in Thailand - Kuptawintu, Santi; U-on, Vichit (Rajapark Journal, 2024)
This research aimed to 1) study the factors of service quality, marketing, and brand value that affect the customer experience of B2B drugstore owners in Thailand, 2) study the influence of Causal factors of service quality, marketing, and brand value on the customer experience of B2B drugstore owners in Thailand, and 3) build a model of causal factors of service quality, marketing, and brand value that affect the customer experience of B2B drugstore owners in Thailand. This research utilized a mixed methods approach, incorporating both quantitative and qualitative research, as well as explanatory research. The samples used in the study were 5 purposive random samples and 420 samples from 22,122 drugstores in Thailand. The researchers analyzed the results from in-depth and semi-structured interviews. The researchers developed questions focused on the components or variables at a specific level. If the interviews revealed other interesting topics, follow-up interviews or inquiries would be conducted on those issues. The research findings indicated two key points: 1) It is beneficial for pharmaceutical companies to utilize marketing mixes, as this not only enhances the experiences of pharmacies but also positively affects various factors. 2) There is a close relationship among service quality, marketing mix, and brand value. The quality of service and the implementation of suitable marketing mixes contribute significantly to the creation and enhancement of brand value.